Encyclopedia of Life Sciences 2013
DOI: 10.1002/9780470015902.a0024618
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Uric Acid Metabolism in Humans

Abstract: Several evolutionary changes have led to uric acid levels being much higher in humans than in other mammals. Uric acid is the end product of purine metabolism in hominoids, including humans, due to the genetic loss of uricase activity during the Miocene epoch, and this is the main cause of the increased uric acid in hominoids. Additional factors that have contributed to increased levels of uric acid are the high renal tubular reabsorption of uric acid and the previous loss of the ability to synthesise vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
(54 reference statements)
0
1
0
1
Order By: Relevance
“…Hidrogen peroksida tersebut akan bereaksi dengan DHBSA dan 4-aminoantipirin membentuk senyawa berwarna yang kadarnya setara dengan kadar asam urat. Urikase merupakan enzim yang spesifik mengubah asam urat menjadi alantoin (Lario dan Vicenta, 2010). Sehingga urikase tidak dapat bereaksi dengan senyawa fenol dan tidak menghasilkan hidrogen peroksida.…”
Section: Analisis Dataunclassified
“…Hidrogen peroksida tersebut akan bereaksi dengan DHBSA dan 4-aminoantipirin membentuk senyawa berwarna yang kadarnya setara dengan kadar asam urat. Urikase merupakan enzim yang spesifik mengubah asam urat menjadi alantoin (Lario dan Vicenta, 2010). Sehingga urikase tidak dapat bereaksi dengan senyawa fenol dan tidak menghasilkan hidrogen peroksida.…”
Section: Analisis Dataunclassified
“…Unlike ascorbate, uric acid is largely regarded as end-product of purine metabolism and metabolic waste [5]. Yet, human-biased research has suggested alternative physiological functions for uric acid or urate (uric acid salts), such as antioxidant and free radical scavenger, similarly to ascorbic acid, counterbalancing disease-related oxidative stress [6][7][8].…”
Section: Introductionmentioning
confidence: 99%